Measuring the Effectiveness of HRIS in the Indian IT Industry using Structural Equation Modelling - Anil Kumar Singh, Manmohan Mall, Prataprudra Parida (International Journal of Advanced Science and Technology, 2020)
This research aims at establishing a relationship between the factors affecting the effectiveness of the Human Resource Information System in Indian IT companies. Eight factors were identified and used in the study. Confirmatory Factor Analysis was conducted, and a Human Resource Information System model was developed using Structural Equation Modelling. A close relationship between the factors affecting the HRIS and the effectiveness of the HRIS in the Indian IT Industry was established. The results of this study provide a decent model fit. Although a Human Resource Information System is treated as an alternative to the paper-based work, yet other functions are still to be exploited. This calls for proper training of personnel in-charge of Human Resource functions as well as customizing the Human Resource Information System as per the requirement for ease of use, resulting in an effective Human Resource Information System by reduction of cost.